Exposition of dermatophyte Trichophyton mentagrophytes to L‐cystine induces expression and activation of cysteine dioxygenase. Issue 11 (13th July 2014) - Kasperova, Alena; Cahlikova, Romana; Kunert, Jiri; Sebela, Marek; Novak, Zdenek; Raska, Milan
Summary Cysteine dioxygenase (CDO) is involved in regulation of intracellular cysteine levels by catabolising the cysteine to sulphite and sulphate. In keratinolytic fungi, sulphite is actively excreted to reduce disulphide bridges in keratin before its enzymatic degradation. The pathogenicity role of CDO was confirmed in cysteine‐hypersensitive and growth‐defective ΔCdo mutant of Arthroderma benhamiae on hair and nails. We analysed the CDO expression regulation in T. mentagrophytes (anamorph of A. benhamiae) mycelia by determining the Cdo mRNA and CDO protein levels and by analysing the proportion of two molecular forms of CDO in response to l‐cystine exposure. Cdo mRNA levels in mycelia lysates were detected by reverse‐transcription real‐time polymerase chain reaction and CDO protein by western blot using mouse CDO‐specific hyperimmune serum. The Cdo mRNA level increased gradually 2.5–4.5 h after exposure of the mycelium to l‐cystine. The CDO protein, detected as two bands of different mobility, appeared earlier in comparison to mRNA (1 h) and culminated after 24 h. More mobile form prevailed after 4.5 h. The comparison of the dynamics in the Cdo mRNA and CDO protein levels indicates that T. mentagrophytes responds to l‐cystine by increased transcription and apparently decreased degradation of the CDO and by changing towards higher mobility molecular form, similar to previous reports describing mammalian analogue.